A Simple and Efficient Microwave-Assisted Synthesis of Substituted Isoindolinone Derivatives via Ligand-Free Pd-Catalyzed Domino C–C/C–N Coupling Reaction - Tyagi, Vikas; Khan, Shahnawaz; Chauhan, Prem M. S. (Synlett, 2013)
We have reported a microwave-assisted, ligand-free Pd-catalyzed domino C–C/C–N coupling reaction to construct diverse isoindolinone derivatives using amides and isocyanides as coupling partners. This strategy provides isoindolinone derivatives in moderate to good yield and high stereoselectivity. A broad range of amides has been tolerated and there is no need for extra-dry conditions in this reaction protocol, which offered highly diverse products and easy handling of the reaction.
Keywords: ligand; Pd-catalyzed; isoindolinone; amides; isocyanides